Synthesis and characterization of nano dicalcium phosphate dihydrate from biogenic sources - Md. Kawcher Alam; Md. Sahadat Hossain; Mofassel Hossen Akash; Muhammad Shahriar Bashar; Newaz Mohammed Bahadur; Samina Ahmed (Results in Materials, 2025)
In the present study, calcium-enriched marine sources (Turritella, Cardium, and Conch shells) were used to prepare dicalcium phosphate dihydrate (DCPD) in an easy, affordable, and sustainable manner. To produce DCPD, orthophosphoric acid was subjected to a reaction with each type of shell powdered substance, resulting in DCPD in a sheet-like or irregular-type shape. The powdered materials were analyzed using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), and Fourier-transform infrared spectroscopy (FT-IR). FT-IR spectroscopy was employed to determine the presence of functional groups in the prepared DCPD. SEM image confirms plate-like structure, indicating homogeneity in both size and shape. EDX spectrum confirms the presence of Ca, P, and O and the degree of purity of all produced materials. The crystallite size of nano DCPD is determined by a variety of XRD models using the XRD pattern. An acceptable measurement for crystallite size was also obtained using the Size-Strain Plot (17.55, 27.18, 35.55 nm) and Halder-Wagner Model (11.23, 13.15, 28.57 nm). Many crystallographic properties of the synthesized substances were examined, including dislocation density, crystallinity index, relative intensity, preference growth, and microstrain. The DCPD percentage obtained by Rietveld refinement analysis is close to 90 %. Therefore, Turritella, Cardium, and Conch shells will provide an alternate source to fulfil the need for raw materials to manufacture DCPD.